Flame-retardant polyester - Galip, H; Hasipoglu, H; Gündüz, G (John Wiley & Sons Inc, 1999)
Halogenation and addition of some heavy metallic oxides have been in use for a few decades to impart flame-retarding properties to polymers. In this study bromine was added to the polymer (polyester of propylene glycol + phthalic anhydride) by means of decabromodiphenyloxide (DBDPO) at varying concentrations. In addition to bromine, 2% antimony oxide (Sb2O3) was also added. In predicting the flame-retarding properties of the polymeric samples prepared, the oxygen index test and the burning rate tests were applied. The results of these tests indicate that the oxygen index values of brominated polyester increase linearly as bromine content increases, and that the polyester containing 2% Sb2O3 in addition to 10-12% Br has a marked flame-retarding property. The mechanical properties were also studied, and some improvement has been observed in mechanical properties by adding acrylonitrile to the polyester. (C) 1999 John Wiley & Sons, Inc.
Keywords: flame retardating properties; polymers; DBDPO